The Influence of Investment Factors, International Trade, and Agricultural Policy on Economic Growth in the Agricultural Sector: A Case Study on a Cattle Farmer in West Java - Arief Budi Pratomo (Westscience Press, 2023)
This research investigates the dynamic interplay of investment factors, international trade, and agricultural policies on the economic growth of cattle farming in West Java. Employing a quantitative approach, data from a sample of 110 cattle farmers were analyzed using regression analysis and SPSS version 26. The findings reveal significant positive relationships between investment factors, international trade, agricultural policies, and economic growth. Increased investments in infrastructure, technology, and human capital, active engagement in international trade, and supportive agricultural policies emerge as key drivers of economic prosperity within the cattle farming sector. The study contributes nuanced insights that can inform targeted interventions and policy formulations for sustainable agricultural development in West Java.